2021
DOI: 10.15587/1729-4061.2021.228960
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive procedure for estimating the stressed-strained state of a reinforced concrete bridge under the action of variable environmental temperatures

Abstract: This paper reports the full-scale experimental measurements of temperature distribution over the surfaces of bridges' steel-concrete beams under the influence of positive and negative ambient temperatures. It has been established that the temperature is distributed unevenly along the vertical direction of a bridge's steel-concrete beam. It was found that the metal beam accepted higher temperature values. The maximum registered temperature difference between a metal beam and a reinforced concrete slab at positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The study of the temperature field in a three-layer model (defective ferroconcrete pipe reinforced with a metal corrugated structure) [20] has established the nonuniformity of temperature distribution across the layers, which leads to a contact effect defined by non-ideal conditions of heat exchange at the junction between the layers. Similar calculation outcomes of temperature fields have been achieved in the studies on multilayered bridge structures [21,22].…”
Section: Literature Reviewsupporting
confidence: 74%
See 1 more Smart Citation
“…The study of the temperature field in a three-layer model (defective ferroconcrete pipe reinforced with a metal corrugated structure) [20] has established the nonuniformity of temperature distribution across the layers, which leads to a contact effect defined by non-ideal conditions of heat exchange at the junction between the layers. Similar calculation outcomes of temperature fields have been achieved in the studies on multilayered bridge structures [21,22].…”
Section: Literature Reviewsupporting
confidence: 74%
“…These papers mainly deal with the heating of the solid through the coating, with the issues of head conduction over the coating and exchange of heat with the solid and the ambient environment not being elaborated on. Papers [20][21][22] present temperature distributions in piecewise inhomogeneous solids and estimate their impact on the strength of structural elements. The study of the temperature field in a three-layer model (defective ferroconcrete pipe reinforced with a metal corrugated structure) [20] has established the nonuniformity of temperature distribution across the layers, which leads to a contact effect defined by non-ideal conditions of heat exchange at the junction between the layers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The influence of temperature on the stressed state of bridges is described in [15]. It was established that at the border of various metal beams and reinforced concrete slabs there is a jump in temperature stresses.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The studies carried out [2,7,[10][11][12][13][14][15][16][17][18][19] identified the main prefabricated units and parts that fail: engine, gearbox, synchronizer, vibration exciter, propeller shafts, couplings, photographs of such failures are shown in Fig. 7.17.…”
Section: Research Of Indicators Of Reliability Of Technical Systemsmentioning
confidence: 99%